Faithful reflections: Understanding LGBT spirituality - Leman, Theresia Zefany Hope Leman; Tobing, David Hizkia (Talenta Publisher, 2024)
Spirituality is one aspect of transpersonal psychology that cannot be separated. Spirituality involves a search for the transcendent. The experience of spirituality can be felt by all individuals, including by LGBT people who are considered by society to be against religious norms. The meaning of God felt by LGBT people is undoubtedly different. This study aims to describe the spirituality experienced by LGBT people. The literature review was conducted on lesbian, gay, bisexual, and transgender subjects. The results of the literature review found that LGBT individuals have an understanding of religious values that affect their experience of spirituality. The way they get closer to God is not only by praying, worshiping, and visiting synagogues but also by implementing humanitarian values for others. This study shows how LGBT people experience spirituality.